A Strategy for Instilling Moral Values Through Psychomotor Fiqh Instruction at Nurayin Middle School Using a Descriptive Qualitative Approach - Wati, Linda; Yansah, Alrudi; Muttaqin, Muttaqin (UIR Press, 2026)
This study aims to formulate a strategy for internalizing moral values through psychomotor-based fiqh learning at Madrasah Tsanawiyah Nurayin and to evaluate its effectiveness in enhancing students’ practical skills. The study is motivated by the gap between students’ cognitive understanding of moral values and their implementation in daily activities. A qualitative descriptive approach was adopted, with subjects consisting of fiqh teachers and ninth-grade students selected purposively. Data were collected through observation, semi-structured interviews, and documentation, and analyzed using the interactive model of Miles and Huberman (1994) through data reduction, data display, and verification. Findings indicate that a learning strategy combining worship practices, reflection on meaning, habituation, and teacher modeling can improve the consistency of students’ ethical behavior and psychomotor skills. The learning process encourages a shift from normative compliance to reflective moral awareness, although the degree of internalization varies. The study concludes that moral value internalization is effective when supported by a consistent school culture, psychomotor evaluation, and learning that integrates cognitive, affective, and practical aspects. This research contributes to the implementation of the Merdeka Curriculum in fiqh education through a reflective-transformative model that integrates ethical values and practical skills, making learning more contextual, applicable, and impactful in students’ daily lives.